2008, No.3, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2019)
Jonas Mackevičius, The regulation of financial accounting in Lithuania during the Soviet occupation (1966–1989) , 7Vita Daubarienė, Kristina Rudžionienė, The selection of evaluation methods representing true and fair view of a financial performance of a company, 18Darius Gliaubicas, The research of management accounting methods in Lithuanian companies, 32Romualdas Valkauskas, Economic fluctuations: indicators, statistical description, 52Vladislav Tomaševič, The main principles of policy formation of working capital management, 61Martynas Novikovas, Application of Berry ratio in transfer pricing, 74Romualdas Bartaška, Liuda Gargasienė, External and internal audit of projects financed by EU funds, 81Agnė Ramanauskaitė, Exposure of intellectual capital in financial report of a company, 94
Keywords: none